1959
DOI: 10.1002/pol.1959.1203613015
|View full text |Cite
|
Sign up to set email alerts
|

Thermal degradation of polyethylene oxide and polypropylene oxide

Abstract: Polyethylene oxide and atactic and isotactic polypropylene oxides were pyrolyzed in a vacuum in the temperature range 265 to 363°C. One phase of the investigation consisted in fractionating the products of degradation and analyzing the fractions qualitatively and quantitatively. Another phase consisted in measuring rates of degradation and calculating from these rates the activation energies. As compared with the corresponding non‐oxide polymers, polyethylene and polypropylene, the oxide polymers are less stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
0
2

Year Published

1991
1991
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(49 citation statements)
references
References 7 publications
7
40
0
2
Order By: Relevance
“…4 shows that the content of end group VIII for p-PEG is less than other end groups, which show that the dominating type of bond cleavage within PEG under 350 8C is C-O cleavage. This result is agree with the reported results of low-temperature PEG pyrolysis [1,4]. The decrease of end group VIII after adding nano-Co 3 O 4 reveals that the nano-Co 3 O 4 enhances the C-O bond cleavage and enlarges the ratio of C-O cleavage to C-C cleavage.…”
Section: Resultssupporting
confidence: 95%
See 2 more Smart Citations
“…4 shows that the content of end group VIII for p-PEG is less than other end groups, which show that the dominating type of bond cleavage within PEG under 350 8C is C-O cleavage. This result is agree with the reported results of low-temperature PEG pyrolysis [1,4]. The decrease of end group VIII after adding nano-Co 3 O 4 reveals that the nano-Co 3 O 4 enhances the C-O bond cleavage and enlarges the ratio of C-O cleavage to C-C cleavage.…”
Section: Resultssupporting
confidence: 95%
“…Madorsky and Straus identified low-molecular weight PEG pyrolyzates, including formaldehyde, ethanol, poly(ethylene oxide), carbon dioxide and water for the pyrolysis temperatures around 350 8C [1]. Two major chain scission types of thermal degradation pathways they proposed were: ''Type 1'' scission involving an intramolecular transfer of hydrogen produced both a saturated and an unsaturated end group; ''Type 2'' scission involving a homolytic C-O cleavage yielded polymer fragments terminated by radicals.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…carbonyl group), no such increase was observed for the other vacuum-annealed samples when compared with an unannealed standard. In agreement with these infrared spectroscopy results, Kelleher et al [22] found similar absorption bands for PXE heated to 125 ~ in air, while Madorsky [23] and Madorsky and Straus [24] observed that PXE annealed under vacuum was stable at 320 ~ Thus it appears that the decrease in bromine yield near the surface of PXE (see Fig. 5) can be attributed to the deactivation of the phenylene ring due to an oxidation reaction.…”
Section: Methodssupporting
confidence: 60%
“…Many aspects of PEG degradation have been studied. It has been shown that a number of factors affect the degradation as for example different kinds of electromagnetic radiation (Decker and Marchal, 1974;Gardette, 2001, 2003;Vijayalakshmi et al, 2005a,b), electromagnetic radiation or heat in combination with the presence of salts (Costa et al, 1992;Gjurova et al, 1997Gjurova et al, , 1999Glastrup and Padfield, 1993;Kaczmarek, 1996;Kaczmarek et al, 1999Kaczmarek et al, , 1996Kaczmarek et al, , 2001Kaczmarek and Rabek, 1997;Kaminska et al, 1999;Lloyd, 1963;Rabek et al, 1992), unassisted pyrolysis and oxidation has also been investigated (Bilz et al, 1994;Dulog and Storck, 1966;Evetts et al, 1995;Fares et al, 1994;Geymayer et al, 1991;Glastrup, 1996;Goglev and Neiman, 1967;Grassie and Mendoza, 1984;Han et al, 1995Han et al, , 1997Hoffmann et al, 1984;Kaczmarek et al, 2000;Lattimer, 2000;Madorsky and Straus, 1959;Mcgary, 1960;Heatley, 2002, 2004;Neto et al, 2002;Padfield et al, 1990;Scheirs et al, 1991;Voorhees et al, 1994;Yang et al, 1996). Oxidation of PEG can take place at relatively low temperatures (Bilz et al, 1994;Geymayer et al, 1991;…”
Section: Introductionmentioning
confidence: 97%